TRANSFORMASI ADMINISTRASI SEKOLAH BERBASIS DIGITAL: STUDI KEPUSTAKAAN TENTANG IMPLEMENTASI, PROBLEMATIKA, DAN KEMANFAATAN DAPODIK DALAM MANAJEMEN PENDIDIKAN - Irawan, Irsad; Nurdiansyah, Sidik; Rosmaladewi, Okke (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital transformation in the education sector has shifted the data management paradigm from a conventional system to an integrated one. This study aims to analyze in depth the implementation, challenges, and benefits of the Basic Education Data (Dapodik) application as the primary instrument for school administration in Indonesia. Using library research, this article examines various literature, regulations, and previous research reports relevant to the digitalization of education management. The study's findings indicate that the implementation of Dapodik has successfully created national data standardization, facilitating efficiency in the distribution of operational assistance funds, mapping of infrastructure, and updating of educator data. However, this transformation process still faces significant challenges, including limited technological infrastructure in remote areas, high administrative burdens for school operators, and data validity issues related to population system synchronization. Nevertheless, Dapodik's usefulness as the backbone of education management is crucial in supporting data-driven policies. This study concludes that strengthening digital literacy among administrative staff and improving the stability of the application system are key to optimizing Dapodik's role as a catalyst for transparent and accountable school administration transformation.